Ripple mapping: Initial multicenter experience of an intuitive approach to overcoming the limitations of 3D activation mapping. (29th August 2017) - Luther, Vishal; Cortez‐Dias, Nuno; Carpinteiro, Luís; de Sousa, João; Balasubramaniam, Richard; Agarwal, Sharad; Farwell, David; Sopher, Mark; Babu, Girish; Till, Richard; Jones, Nikki; Tan, Stuart; et al.
Abstract: Background: Ripple mapping (RM) displays electrograms as moving bars over a three‐dimensional surface displaying bipolar voltage, and has shown in a single‐center series to be effective for atrial tachycardia (AT) mapping without annotation of local activation time or window‐of‐interest assignment. We tested the reproducibility of these findings in operators naïve to RM, using it for the first time in postablation AT. Methods: Maps were collected with multielectrode catheters and CARTO ConfiDENSE. A diagnosis of the tachycardia mechanism was made using RM and an assessment of operator confidence was made according to a three‐grade scale (1 highest—3 lowest). Results: The first 20 patients (64 ± 9 years, median two previous ablations) undergoing RM‐guided AT ablation across five sites were studied. High‐density maps (2, 935 ± 1, 328 points) in AT (CL = 296 ± 95 milliseconds) were collected. Macroreentrant ATs bordered by scar or anatomical obstacles were identified in n = 12 (60%), small reentrant ATs around scar in n = 3 (15%), and focal ATs from scar in n = 5 (25%). Diagnostic confidence with RM was grade 1 in n = 13 (65%), where operators felt confident to proceed to ablation without entrainment. Ablation offered the correct diagnosis n = 18 (90%). Retrospective review of the accompanying LAT maps demonstrated potential sources for error related to the window of interest selection, interpolation, and differentiating regions of scar during tachycardia on the voltage map. Conclusion: RM was easy to adopt by operators using it for the first time, and identified the correct target for ablation with high diagnostic confidence in most cases of complex AT.